2020
DOI: 10.1107/s2053229620014217
|View full text |Cite
|
Sign up to set email alerts
|

First COVID-19 molecular docking with a chalcone-based compound: synthesis, single-crystal structure and Hirshfeld surface analysis study

Abstract: The first example of molecular docking of the SARS-CoV-2 main protease for COVID-19 [Mpro, Protein Data Bank (PDB) code 7BQY] by a chalcone-based ligand, namely, (E)-1-(2,4-dichlorophenyl)-3-[4-(morpholin-4-yl)phenyl]prop-2-en-1-one, C19H17Cl2NO2, I, is presented. Two-dimensional (2D) LIGPLOT representations calculated for the inhibitor N3, viz. N-{[(5-methylisoxazol-3-yl)carbonyl]alanyl}-L-valyl-N 1-((1R,2Z)-4-(benzyloxy)-4-oxo-1-{[(3R)-2-oxopyrrolidin-3-yl]methyl}but-2-enyl)-L-leucinamide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…We have also determined the enrichment ratios (ER) of the intermolecular contacts for DZ1 and DZ2 compounds to reveal the propensity of two chemical species to be in contact [50] . Table 2a - 2b presents the E XY values for the two molecules derived from the Hirshfeld surface analysis results.…”
Section: Resultsmentioning
confidence: 99%
“…We have also determined the enrichment ratios (ER) of the intermolecular contacts for DZ1 and DZ2 compounds to reveal the propensity of two chemical species to be in contact [50] . Table 2a - 2b presents the E XY values for the two molecules derived from the Hirshfeld surface analysis results.…”
Section: Resultsmentioning
confidence: 99%
“…It could be concluded from this example that the better interaction, the lower the binding affinity [43]. A key to the symbols is reported before [45]. The cutoff for the nonbonded interactions is 3.9 Å.…”
Section: Docking Studymentioning
confidence: 88%
“…Comparative docking analysis was carried out to evaluate each ligand's display, after docking, in light of different Y groups (Scheme 1, Figure 9). Surprisingly, although all ligands possessed the same 1,2,3-triazole motif, the ligands interacted differently against 7BQY due to, probably, the different Y group at the para position of each ligand (Figure A key to the symbols is reported before [45]. The cutoff for the nonbonded interactions is 3.9 Å.…”
Section: Docking Studymentioning
confidence: 89%
See 1 more Smart Citation
“…Interaction of these flavonoids with ACE2 may also impede the binding of SARS-CoV-2 spike protein and is in line with the anti-viral properties of these compounds [149].The interaction of flavonoids with Mpro, Spike receptor binding domain (Spike-RBD), RNA -dependent RNA polymerase (RdRp or Nsp12), non-structural protein 15 (Nsp15) and the host ACE-2 spike-RBD binding domain have been examined using advanced computation molecular docking techniques. These en-silicoSARS-CoV-2 binding studies indicated that tribuloside, legalon and isosilybin had anti-viral antiinfective properties, warranting further evaluation to determine how effective they are in the inhibition of SARS-CoV-2 infectivity [150].A range of chalcone derivatives have been evaluated using molecular docking methods to assess the effectiveness of these re-purposed compounds on the prevention of the infectivity and replication of SARS-CoV-2 [151][152][153][154][155].…”
Section: A) Anti-viral Properties Of Plant Phytochemicals Against Sars-cov-2 Viral Functionsmentioning
confidence: 99%